Second language acquisition in action principles from practice - Nava, Andrea; Pedrazzini, Luciana (Bloomsbury Academic, 2018)
"Second Language Acquisition in Action identifies eight important SLA principles and involves readers in an 'experiential' approach which enables them to explore these principles 'in action'. Each chapter is structured around three stages: experience and reflection; conceptualisation; and restructuring and planning. Discussion questions and tasks represent the core of the book. These help readers in the process of 'experiencing' SLA research and provide them with opportunities to try their hands at different areas of language teachers' professional expertise."--Provided by publisher.